1990
DOI: 10.1159/000186122
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Exercise Responses in Ciclosporin-Treated Normotensive Renal Transplant Recipients

Abstract: Although many patients taking ciclosporin (CS) for the long term develop hypertensive side effects, a proportion do not. We have studied the blood pressure response to graded upright bicycle exercise while continuously recording the metabolic rate in 18 normotensive renal transplant recipients whose mean age was 30.8 years (range 16–54). Nine were treated with CS alone and 9 with azathioprine and a steroid, prednisolone (AzS). Both groups performed a progressive exercise test, with work increasing by 25 W ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Scott et al [12] reported that blood pressure during exercise was higher in nine adult renal transplant patients on CyA therapy when compared to nine similar patients on therapy with azathioprine and prednisone. We hypothesize that during exercise an increase in peripheral vascular tone occurs in patients receiving CyA treatment [5].…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al [12] reported that blood pressure during exercise was higher in nine adult renal transplant patients on CyA therapy when compared to nine similar patients on therapy with azathioprine and prednisone. We hypothesize that during exercise an increase in peripheral vascular tone occurs in patients receiving CyA treatment [5].…”
Section: Discussionmentioning
confidence: 99%